Arthropod diversity and abundance on a suburban remnant of the Shortgrass Steppe - Hartley, Laurel, author; SGS-LTER, Colorado State University, publisher (Colorado State University. Libraries, 2005)
Arthropod censuses are recorded on the Shortgrass Steppe Long Term Ecological Research site and Pawnee National Grasslands as a part of long term ecological monitoring. As the front range becomes developed, remnants of the shortgrass steppe become surrounded by human habitation. Subsequently there are increased efforts to control "pest" insect species, an increase in water availability, changes in insect food sources, and changes in predator species. These environmental changes are likely to affect arthropod communities. Long term monitoring of arthropod communities on a remnant shortgrass steppe enclosed by development may provide baseline data useful for local agencies creating management plans for natural areas along the front range.

Compiled by Rocky Mountain High School biology students in collaboration with the staff, graduate students, and faculty associated with the Shortgrass Steppe Long Term Ecological Research Program.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Colorado State University. Natural Resource Ecology Laboratory; Colorado State University. Department of Forest and Rangeland Stewardship; Colorado State University. Department of Soil and Crop Sciences; Colorado State University. Department of Biology; California State University, Fullerton; United States. Agricultural Research Service; University of Northern Colorado; Rocky Mountain High School.
Keywords: shortgrass steppe; long term ecological research; grassland ecology; Pawnee National Grassland; Central Plains Experimental Range; arthropods